Analisis Social Media Marketing dan Tampilan Produk Dalam Meningkatkan Penjualan Produk Pamos Shop Mojokerto - Ayu Setianingtyas; Eka Indah Nurlaili (Jurnal Manajemen dan Bisnis, 2020)
Pamos Shop Mojokerto is an outlet business that sells a variety of women's needs. This outlet sales have decreased during 2019. The comparison between sales of products by online and offline are 65%:35%. In this study, authors wanted to find out the effect of social media marketing and product display on sales increases at Mojokerto Pamos Shop. This study uses a multiple linear regression research model by accidental sampling to get the samples. Data collected by distributing questionnaires that containing 18 statement items to 100 respondents. The techniques that uses to data processing are descriptive analysis, classical assumption test, and hypothesis testing. The results showed that the effect of social media marketing and product display on sales increases at Mojokerto Pamos shops was 30.3%. Based on the results of hypothesis testing, two variables are influence by simultaneously on sales increases. However, partial test results show that only product display variables have a significant effect on sales increases. The test results also show that product display has a more dominant influence on sales increase. This shows that so far Pamos Shop Mojokerto must has maximized social media marketing in an effort to increase sales.